2020
DOI: 10.1172/jci130015
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial CagA protein compromises tumor suppressor mechanisms in gastric epithelial cells

Abstract: Approximately half of the world's population is infected with the stomach pathogen Helicobacter pylori. Infection with H. pylori is the main risk factor for distal gastric cancer. Bacterial virulence factors, such as the oncoprotein CagA, augment cancer risk. Yet despite high infection rates, only a fraction of H. pylori-infected individuals develop gastric cancer. This raises the question of defining the specific host and bacterial factors responsible for gastric tumorigenesis. To investigate the tumorigenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 45 publications
(68 reference statements)
0
36
0
Order By: Relevance
“…Interestingly, the dysregulation of p53 occurs in a strain-specific manner, with tumorigenic H. pylori strains having a stronger ability to affect p53 [ 40 , 43 ]. Tumorigenic H. pylori strains also decrease activity of other tumor suppressors: p14ARF, SIVA1, and p27(KIP1) [ 43 , 44 , 45 , 46 ].…”
Section: H Pylori and Gastric Cancermentioning
confidence: 99%
“…Interestingly, the dysregulation of p53 occurs in a strain-specific manner, with tumorigenic H. pylori strains having a stronger ability to affect p53 [ 40 , 43 ]. Tumorigenic H. pylori strains also decrease activity of other tumor suppressors: p14ARF, SIVA1, and p27(KIP1) [ 43 , 44 , 45 , 46 ].…”
Section: H Pylori and Gastric Cancermentioning
confidence: 99%
“…Recurrent bacterial, viruses and fungal infections are some of the major factors. Chronic inflammation triggered by persistence of H. pylori is often preceding gastric cancer appearance ( 277 279 ), a phenomenon drastically worsened in some PID patients ( 280 , 281 ). Similar observations were made for fungal infections ( 282 ) or for the Epstein Barr Virus, as recently highlighted in another special issue of Frontiers In Immunology ( 283 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that the H. pylori virulence factor CagA could influence the Siva1 protein via increasing ubiquitination and proteasomal degradation mediated by the activation of the PI3K/Akt pathway and XIAP E3 ubiquitin ligase [ 110 ]. The data also suggested a downregulation of Siva1, causing inhibition of the apoptotic and DNA damage responses induced by H. pylori , whereas CagA was found to inhibit the apoptotic cell death promoting the survival of damaged epithelial cells that contributes to gastric tumorigenesis [ 110 ].…”
Section: Caga-dependent Mechanisms Of Pathogenicitymentioning
confidence: 99%